Frequency of Cardiac Complications in Thalassemia Major Patients - Sarwar, Hamna; Sheikh, Saifullah; Chaudhary , Hafsa; Asif, Aroosha (Indus Journal of Bioscience Research, 2025)
Background: Thalassemia major (TM) is a genetic hemoglobinopathy characterized by chronic anemia and iron overload due to frequent blood transfusions. Cardiac complications are a significant cause of morbidity and mortality in these patients, primarily due to iron accumulation in the heart. Early identification and management of these complications are essential to improve outcomes. Objectives: To assess the frequency and types of cardiac complications in children with beta-thalassemia major and to identify their association with age, gender, duration of transfusion, and serum ferritin levels. Study Settings: Department of Pediatrics, Allied Hospital Faisalabad. Duration of Study: 10th May 2024 to 9th November 2024. Data Collection: This cross-sectional study included 110 children aged 5–15 years with confirmed beta-thalassemia major, who had received at least five blood transfusions. Data collection involved clinical history, examination, serum ferritin levels, electrocardiography, and echocardiography to evaluate cardiac complications. Cardiac complications were categorized into cardiomegaly, congestive cardiac failure, cardiomyopathy, and pulmonary hypertension. Results: The frequency of cardiac complications was 60.45%, with cardiomegaly being the most common (51.85%), followed by congestive heart failure (24.69%), cardiomyopathy (14.81%), and pulmonary hypertension (8.64%). Cardiac complications were more frequent in patients with transfusion duration >5 years (64.49%, p=0.057) and serum ferritin ≤15 µg/ml (70.59%, p=0.162). However, age, gender, and serum ferritin levels were not significantly associated with cardiac complications. Conclusion: Cardiac complications are common in beta-thalassemia major patients, with cardiomegaly being the most frequent. Early screening and management of these complications are crucial to reduce morbidity and mortality in this high-risk population.